SMART ROAD TRAFFIC MANAGEMENT SYSTEM - V., Deepak; Joseph, Christeena (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, the smart way of traffic control is achieved. The proposed system uses a traffic module that is connected to the Arduino. The module is implemented in a “+” junction where the quick movement of vehicles can be obtained. In the proposed system, components like Arduino Mega, Traffic Module, Wi-Fi Module, LED (light-emitting diodes), and IR sensors are used. The system is based on IoT so that the traffic signals can be monitored continuously. This is implemented in the movement of the ambulance during high traffic hours so that the ambulance can reach in time to its desired location without getting stuck in the traffic for a long time. Also, the changes in the traffic module can be observed continuously.